2016
DOI: 10.1016/j.rdc.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcomes in Psoriatic Arthritis

Abstract: SYNOPSIS Patient reported outcome (PRO) measures are an important component to assessing disease impact and therapy response in patients with psoriatic arthritis (PsA). Overall there are few PsA-specific PROs. Most PROs used in PsA are borrowed from other diseases (e.g. rheumatoid arthritis and ankylosing spondylitis) or general population PROs. PROs are used in PsA clinical trials and in the clinical management of PsA. In this review, we discuss the most commonly used PRO in PsA including their inclusion in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 85 publications
2
47
0
4
Order By: Relevance
“…Although clinical and laboratory variables are used to measure disease activity and severity, patient-reported outcome (PRO) measures are equally important and represent a critical firsthand account of the patient's perception of well-being and response to treatment 13 . Some of the PRO instruments used in PsA clinical trials were initially created for other diseases 14,15,16,17 ; other generic PRO instruments are also used in PsA trials with the goal of characterizing overall population health, including the Medical Outcomes Study 36-Item Short Form Survey (SF-36) 18 .…”
Section: Rheumatologymentioning
confidence: 99%
“…Although clinical and laboratory variables are used to measure disease activity and severity, patient-reported outcome (PRO) measures are equally important and represent a critical firsthand account of the patient's perception of well-being and response to treatment 13 . Some of the PRO instruments used in PsA clinical trials were initially created for other diseases 14,15,16,17 ; other generic PRO instruments are also used in PsA trials with the goal of characterizing overall population health, including the Medical Outcomes Study 36-Item Short Form Survey (SF-36) 18 .…”
Section: Rheumatologymentioning
confidence: 99%
“…[6,10] This is indeed warranted as several of the PROMs with elusive measurement properties are widely used in PsA trials and clinics today. [77] Some COS domains may be more appropriately assessed by non-PROM instruments such as biomarkers and clinical assessments, and parallel work streams within GRAPPA-OMERACT are collecting psychometric evidence for the use of such tools in PsA. These research initiatives will in addition to the psychometric evidence for PsA PROMs presented in this review inform the consecutive stages of developing a COMS for PsA.…”
Section: Discussionmentioning
confidence: 95%
“…While previous studies have provided overviews of commonly used instruments in PsA, [76,77] this review provides a systematic identification, characterization and evidence synthesis of measurement properties of all PROMs evaluated in PsA, which constitutes an important step in the GRAPPA-OMERACT process of developing a PsA COMS.…”
Section: Discussionmentioning
confidence: 99%
“…Primary results from the trial have been previously reported. 1 Results: In total, 1090 patients were randomised. Of the 313 patients randomised to ETN, by Week 28 there were 83 partial responders and 39 nonresponders.…”
mentioning
confidence: 99%
“…The RAPID3 was originally developed for use in patients with rheumatoid arthritis, but it may be used in clinical practice to assess disease activity in patients with PsA. 1 The PROMIS10 is a general (nondisease-specific) PRO instrument that measures physical, mental, and social health. 2 Developed for the general population, PROMIS10 has not yet been specifically validated in PsA.…”
mentioning
confidence: 99%